1997
DOI: 10.1017/s0025315400071848
|View full text |Cite
|
Sign up to set email alerts
|

Trophic relationships between two gurnards Trigla lucerna and Aspitrigla obscura from the western Mediterranean

Abstract: The feeding habits of Trigla lucerna L. (1758) and Aspitrigla obscura L. (1764) (Pisces: Triglidae), off the coast of the Gulf of Valencia (Spain), were investigated between October 1989 and January 1991. The two species examined in this study appear to have distinct feeding types, based on the species composition of prey and the frequency of occurrence of major food items. Tub gurnard had a more diverse diet and fed mainly on crustaceans (mysids and decapods), teleosts and molluscs, whilst long fin gurnard w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
8
22
0
Order By: Relevance
“…A comparison between the diets of the three predators has evidenced the widest prey variety in C. lucerna; said array is mainly made up of epibenthic and infaunal organisms encompassing a variety of crustaceans, molluscs and fish that are typical of soft bottoms. Said feeding behaviour is in line with what reported in literature for this species in other areas (Collignon and Aloncle 1960;Colloca et al 1994;Costa 1988;Morte et al 1997;Stagioni et al 2011), although prey composition may vary depending on local resource availability.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A comparison between the diets of the three predators has evidenced the widest prey variety in C. lucerna; said array is mainly made up of epibenthic and infaunal organisms encompassing a variety of crustaceans, molluscs and fish that are typical of soft bottoms. Said feeding behaviour is in line with what reported in literature for this species in other areas (Collignon and Aloncle 1960;Colloca et al 1994;Costa 1988;Morte et al 1997;Stagioni et al 2011), although prey composition may vary depending on local resource availability.…”
Section: Discussionsupporting
confidence: 89%
“…Such intervals were identified taking into account the size at which each species undergoes sexual maturity: (1) S. notata undergoes maturity at about 10-14 cm L T (Scarcella et al 2011b); (2) C. lucerna starts maturing at sizes [180 mm L T (Montanini et al 2008;Morte et al 1997). The specimens of S. porcus collected in our study, except for only one specimen of 90 mm L T , exceeded the size at first maturity reported in literature (i.e.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore apparent that size-related shifts in diet have not been recorded for all gurnard species or may be region specific. Similar to our study, Morte et al (1997) reported that two gurnard species (Tub Gurnard Chelidonichthys [Trigla] lucerna and Longfin Gurnard) off the coast of Spain (Gulf of Valencia) showed little size-related changes in diet. Similarly, Redbanded Searobins from southeastern Korea showed no size-related change in diet with respect to prey type, but the number of prey items consumed increased with increasing body size (Baeck et al 2011).…”
Section: Intraspecific Changes In Dietsupporting
confidence: 91%
“…It is important to obtain this information to formulate a balanced diet that includes feedstuffs able to cover metabolic requirements, and provide a quality end product that will be purchased by consumers. The feeding habits of tub gurnard has been investigated, and it has been ascertained that this species exhibits opportunistic foraging behaviour, mainly preying on epibenthic and nectobenthic organisms (Colloca et al, 1994;Morte et al, 1997;Serena et al, 1998;Stagioni et al, 2012) that are rich in essential fatty acids (Dalsgaard et al, 2003).…”
Section: Introductionmentioning
confidence: 99%